PERLINDUNGAN HUKUM TERHADAP KREDITUR PENERIMA JAMINAN FIDUSIA DALAM BENTUK DAFTAR PIUTANG - ROTUA HOTMAULI S. (PREMISE LAW JURNAL, 2015)
The legal position of the credit list was as the object of additional collateral guaranteeing the order and the smoothness of the payment of the debtor’s debt made in the binding accesoir agreement, then legal protection for the creditor as the fiduciary collateral receiver is regulated Article 15, Article 17, Article 23 paragraph (2), Article 24, Article 27 and Article 29 of Law No.42/1999 on Fiduciary Collateral, and the responsibility of the fiduciary giver as debtor is to maintain the collateral in the forms of accounts receivable and if the party whose name is listed in the list of accounts receivable belongs to those who have breached a contract, the debtor (fiduciary giver) must change him/her. It is suggested that to minimize the risk of credit collateral in the forms of the list of the fiduciary collateral-bound accounts receivable, the creditor keeps maintaining the believed and prudent credit principles and provides the debtor with other choices in asking for additional collateral such personal guarantee and corporate guarantee. Keywords : Legal Protection, Fiduciary Collateral, List of Accounts Receivable.